Daughter's Return : African-American and Caribbean Women's Fictions of History. - Rody, Caroline (Oxford University Press, 2001)
This work offers an analysis of an emerging genre in African-American and Caribbean fiction: the novels of black women writers who have returned to their ancestral past. In novels like Toni Morrison's ""Beloved"", Jean Rhys' ""Wide Sargasso Sea"", and Maryse Conde's ""I, Tituba"", ""magical"" black daughters return to sites of trauma through visions, dreams, and memories. Rody reads these texts as allegorical expressions of the desire of writers newly emerging into cultural authority to reclaim their difficult inheritance, and finds a counter-plot of heroines' encounters with women of other r.